Evaluation of enrichment method for the detection of Vibrio cholerae O1 using a rapid dipstick test in Bangladesh. Issue 3 (9th January 2014) - George, Christine M.; Rashid, Mahamud‐ur; Sack, David A.; Bradley Sack, R.; Saif‐Ur‐Rahman, K. M.; Azman, Andrew S.; Monira, Shirajum; Bhuyian, Sazzadul I.; Zillur Rahman, K. M.; Toslim Mahmud, M.; Mustafiz, Munshi; Alam, Munirul
Abstract Background To evaluate the specificity of the Crystal VC dipstick test for detecting cholera. Methods We compared direct testing using the Crystal VC dipstick test and testing after enrichment for 6 h in alkaline peptone water (APW) to bacterial culture as the gold standard. Samples positive by dipstick but negative by culture were also tested using PCR. Results Stool was collected from 125 patients. The overall specificities of the direct testing and testing after 6‐h enrichment in APW compared to bacterial culture were 91.8% and 98.4% (P = 0.125), respectively, and the sensitivities were 65.6% and 75.0% (P = 0.07), respectively. Conclusion The increase in the sensitivity of the Crystal VC kit with the use of the 6‐h enrichment step in APW compared to direct testing was marginally significant. The Crystal VC dipstick had a much higher specificity than previously reported (91–98%). Therefore, this method might be a promising screening tool for cholera outbreak surveillance in resource‐limited settings where elimination of false‐positive results is critical.